Trichostatin D as a Novel KLF2 Activator Attenuates TNFα-Induced Endothelial Inflammation - Lei, Lijuan; Chen, Minghua; Wang, Chenyin; Jiang, Xinhai; Li, Yinghong; Wang, Weizhi; Li, Shunwang; Zhao, Liping; Sheng, Ren; Han, Jiangxue; Zhang, Yuyan; Chen, Yuchuan; et al. (International journal of molecular sciences, 2022)
Krüppel-like factor 2 (KLF2) is an atherosclerotic protective transcription factor that maintains endothelial cell homeostasis through its anti-inflammatory, anti-oxidant, and antithrombotic properties. The aim of this study was to discover KLF2 activators from microbial secondary metabolites and explore their potential molecular mechanisms. By using a high-throughput screening model based on a KLF2 promoter luciferase reporter assay, column chromatography, electrospray ionization mass spectrometry (ESI-MS), and nuclear magnetic resonance (NMR) spectra, trichostatin D (TSD) was isolated from the rice fermentation of Streptomyces sp. CPCC203909 and identified as a novel KLF2 activator. Real-time-quantitative polymerase chain reaction (RT-qPCR) results showed that TSD upregulated the mRNA level of KLF2 in endothelial cells. Functional assays showed that TSD attenuated monocyte adhesion to endothelial cells, decreased vascular cell adhesion protein 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) expression, and exhibited an anti-inflammatory effect in tumor necrosis factor alpha (TNFα)-induced endothelial cells. We further demonstrated through siRNA and western blot assays that the effects of TSD on monocyte adhesion and inflammation in endothelial cells were partly dependent on upregulating KLF2 expression and then inhibiting the NOD-like receptor protein 3 (NLRP3)/Caspase-1/interleukin-1beta (IL-1β) signaling pathway. Furthermore, histone deacetylase (HDAC) overexpression and molecular docking analysis results showed that TSD upregulated KLF2 expression by inhibiting HDAC 4, 5, and 7 activities. Taken together, TSD was isolated from the fermentation of Streptomyces sp. CPCC203909 and first reported as a potential activator of KLF2 in this study. Furthermore, TSD upregulated KLF2 expression by inhibiting HDAC 4, 5, and 7 and attenuated endothelial inflammation via regulation of the KLF2/NLRP3/Caspase-1/IL-1β signaling pathway.